2013
DOI: 10.3834/uij.1944-5784.2013.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Urethral Stricture Etiology Revisited: An Indian Scenario

Abstract: Objectives: Urethral stricture disease remains a common cause of morbidity among men. Many questions about the etiology of urethral stricture disease remains unanswered till now. This study was done in a tertiary care center along with a review of the literature to evaluate the etiology of urethral strictures and to determine the factors that may influence possible preventive or curative strategies. Methods: This was a retrospective and prospective study of 404 patients with urethral strictures. The case recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Currently, lichen sclerosus is the most common identifiable cause of penile strictures in young and middle-aged men. 8 It causes atrophic fibrosis and is thought to be autoimmune in nature, although an infective aetiology has also been proposed. Typically, lichen sclerosus begins as an itchy white patch on the inner aspect of the foreskin or glans (Figure 2).…”
Section: Aetiologymentioning
confidence: 99%
“…Currently, lichen sclerosus is the most common identifiable cause of penile strictures in young and middle-aged men. 8 It causes atrophic fibrosis and is thought to be autoimmune in nature, although an infective aetiology has also been proposed. Typically, lichen sclerosus begins as an itchy white patch on the inner aspect of the foreskin or glans (Figure 2).…”
Section: Aetiologymentioning
confidence: 99%
“…Urethral catheterization was a more frequent cause than transurethral surgery in this population. [ 2 ] A study comparing characteristics of strictures in men undergoing urethroplasty at leading centers in India and the West suggested that trauma-related strictures were much more common in India (36% vs. 15.8%), whereas the iatrogenic were lesser (16% vs. 35%). The incidence of Lichen Sclerosus (LS)-associated strictures were three times as compared to the western data (21.5% vs. 6.9%).…”
Section: Recommendationsmentioning
confidence: 99%